Critical Examination of International Law Theories - Adama Aloysious Gross (Pan-African Journal of Education and Social Sciences)
This paper examines the complex web of international law and various theories that address its creation, evolution, and usage. This paper critically evaluates many theories to understand what state sovereignty entails, the role played by international institutions, and how compliance has been enforced. By scrutinizing these theories, this paper endeavors to reveal the epistemological structures that underpin the evolution of the science of international law, which may contribute to clarifying the topical discourse concerning the legitimacy, effectiveness, and malleability of the discipline in the context of modern global processes. Glass adventure is initiated by analyzing natural law theory to investigate the presence of universal norms that apply to all inhabitants of the world within the sphere of human relations. The paper then moves to positivist theories, focusing on the state’s consent and formal sources of law as pillars of international legal duties. Moreover, the paper analyzes the realist, fictional, and functional theories of international law. This analysis aims to advance the knowledge of the theoretical underpinnings that influence the development of international law in the modern global environment.